Characterization of Human Herpesvirus 8 genomic integration and amplification events in a primary effusion lymphoma cell line - Álvarez, Eva G.; Otero, Paula; Rodríguez-Martín, Bernardo; Pequeño-Valtierra, Ana; Otero, Iago; Vidal-Capón, André; Rodríguez-Castro, Jorge; Pasantes, Juan J.; Rivas, Carmen; Tubío, Jose M.C.; García-Souto, Daniel (Frontiers in Virology, 2023)
In this study, we investigated the integration of Human Herpesvirus 8 (HHV-8) into the human genome using the primary effusion lymphoma (PEL) cell line BC-3. Through next-generation sequencing (NGS) data from multiple independent sequencing runs, we identified two highly supported HHV-8 integrants. These integrants encompassed a region of human chromosome 12 that was amplified approximately 16-fold between the junctions. Significantly, these events could represent the first known instance of HHV-8 integration into a hybrid human-viral extrachromosomal chimeric circular DNA (eccDNA). The amplified fragment contained partial or complete copies of various human genes, including SELPLG and CORO1C. Analysis of long-read Nanopore data indicated that the CpGs at the SELPLG promoter were mostly unmethylated, suggesting that the additional copies of SELPLG within this eccDNA are likely transcriptionally active. Our findings suggest that viral insertion and eccDNA amplification could be crucial mechanisms in the development of HHV-8-related cancers. In conclusion, our study provides valuable insights into the molecular mechanisms involved in HHV-8-induced oncogenesis and emphasizes the importance of investigating viral integration and eccDNAs in cancer development. Furthermore, we highlight the necessity of employing multiple independent sequencing approaches to validate integration events and avoid false positives derived from library construction artifacts.